GENE-14. UNIQUE MOLECULAR AND CLINICAL FEATURES OF LI-FRAUMENI SYNDROME ASSOCIATED BRAIN TUMOURS. (23rd April 2019) - Zapotocky, Michal; Misove, Adela; Vlckova, Marketa; Krskova, Lenka; Zamecnik, Josef; Vanova, Katerina; Malinova, Bela; Ondrova, Barbora; Pernikova, Ivana; Vicha, Ales; Tichy, Michal; Liby, Petr; et al.
Abstract: Li-Fraumeni syndrome (LFS) is a condition characterized by germ-line TP53 mutation and predisposition to various types of malignant neoplasms in childhood. We aimed to characterize spectrum of brain tumours in children associated with LFS. We gathered clinical information on LFS patients treated since 1990 at our department. Where the tissue was available, we performed molecular analysis consisting of whole genome methylation array and/or sequencing. We identified 15 LFS patients diagnosed with brain tumours; six with choroid plexus carcinoma (CPC), four with glioma, three with medulloblastoma, one PNET and one spinal myxopapilary ependymoma. Twelve of these patients presented with brain tumour as their first malignancy. Two patients were previously treated for rhabdomyosarcoma and developed glioma in radiation field. One patient was diagnosed with medulloblastoma after adrenocortical carcinoma. Out of six patients with CPC, three are alive, with two treated with radiation therapy. Gliomas consisted of three diffuse astrocytomas (DA) and one glioblastoma. DAs were diagnosed at later age (14 to 18 years) and molecularly characterized by rare IDH1 R132G mutation. One glioblastoma was classified as GBM_other using NMP2.0. All four patients are alive with median 4 years from diagnosis of glioma, including the patient with glioblastoma. All medulloblastomas were SHH group with tumor location in the cerebellar hemisphere. Two patients treated with combined radiation and chemotherapy died of secondary malignancy 4 and 5 years from the primary diagnosis. Last patient is currently being treated with radiation sparing approach. In our cohort, majority of patients developed brain tumour as their first malignancy. Radiation sparing approaches need to be implemented to decrease risks of secondary cancers. Gliomas and medulloblastomas seem to harbour distinct molecular features compared to their sporadic counterparts.